Staphylococcus epidermidis Bacteremia Induces Brain Injury in Neonatal Mice via Toll-like Receptor 2-Dependent and -Independent Pathways. (15th April 2015) - Bi, Dan; Qiao, Lili; Bergelson, Ilana; Ek, C. Joakim; Duan, Luqi; Zhang, Xiaoli; Albertsson, Anna-Maj; Pettengill, Matthew; Kronforst, Kenny; Ninkovic, Jana; Goldmann, Donald; Janzon, Anders; et al.
Abstract : Background.   Staphylococcus epidermidis causes late-onset sepsis in preterm infants. Staphylococcus epidermidis activates host responses in part via Toll-like receptor 2 (TLR2). Epidemiologic studies link bacteremia and neonatal brain injury, but direct evidence is lacking. Methods.  Wild-type and TLR2-deficient (TLR2−/−) mice were injected intravenously with S. epidermidis at postnatal day 1 prior to measuring plasma and brain cytokine and chemokine levels, bacterial clearance, brain caspase-3 activation, white/gray matter volume, and innate transcriptome. Results.   Staphylococcus epidermidis bacteremia spontaneously resolved over 24 hours without detectable bacteria in the cerebrospinal fluid (CSF). TLR2−/− mice demonstrated delayed S. epidermidis clearance from blood, spleen, and liver. Staphylococcus epidermidis increased the white blood cell count in the CSF, increased interleukin 6, interleukin 12p40, CCL2, and CXCL1 concentrations in plasma; increased the CCL2 concentration in the brain; and caused rapid (within 6 hours) TLR2-dependent brain activation of caspase-3 and TLR2-independent white matter injury. Conclusions.   Staphylococcus epidermidis bacteremia, in the absence of bacterial entry into the CSF, impairs neonatal brain development. Staphylococcus epidermidis bacteremia induced both TLR2-dependent and –independent brain injury, with the latter occurring in the absence of TLR2, a condition associated with an increased bacterial burden. Our study indicates that the consequences of transient bacteremia in early life may be more severe than commonly appreciated, and our findings may inform novel approaches to reduce bacteremia-associated brain injury.